2020
DOI: 10.3310/hta24080
|View full text |Cite
|
Sign up to set email alerts
|

Plaster cast versus functional bracing for Achilles tendon rupture: the UKSTAR RCT

Abstract: Background Achilles tendon rupture affects > 11,000 people each year in the UK, leading to prolonged periods away from work, sports and social activities. Traditionally, the ruptured tendon is held still in a plaster cast for ≥ 8 weeks. Functional bracing is an alternative treatment that allows patients to mobilise earlier, but there is little evidence about how bracing affects patients’ recovery. Objectives To measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(45 reference statements)
0
11
0
1
Order By: Relevance
“…In 2015, McCormack confirmed not only that dynamic functional rehabilitation, including weightbearing initiated within first two weeks, is safe, but presents higher patient satisfaction and earlier return to activity [ 15 ]. Many authors [ 20 , 25 , 26 , 27 ] suggest that fast rehabilitation programs after open Achilles tenorrhaphy help to accelerate and facilitate the physiological repair process of the tendon suture, encouraging faster recovery of daily life activities, and a return to preinjury sports performance. According to Huang et al [ 28 ], faster mobilization of the ankle joint produces a better restoration of the articular range of motion, with an improvement in local edema, and prevents stiffness and calf atrophy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, McCormack confirmed not only that dynamic functional rehabilitation, including weightbearing initiated within first two weeks, is safe, but presents higher patient satisfaction and earlier return to activity [ 15 ]. Many authors [ 20 , 25 , 26 , 27 ] suggest that fast rehabilitation programs after open Achilles tenorrhaphy help to accelerate and facilitate the physiological repair process of the tendon suture, encouraging faster recovery of daily life activities, and a return to preinjury sports performance. According to Huang et al [ 28 ], faster mobilization of the ankle joint produces a better restoration of the articular range of motion, with an improvement in local edema, and prevents stiffness and calf atrophy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the anatomopathological point of view, when a repaired tendon is subjected to tension during healing, orientation of collagen fibers, strength of the calf muscles, breaking strength of the tendon, number of collagen filaments, and tendon vascularity are all improved [ 26 ]. In addition, the use of supplements and/or drugs (e.g., palmitoylethanolamide, triamcinolone acetonide, or Curcuma) can modulate the human-tendon-derived stem cell activity with potential implications on the tendon healing process [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imputation for data missingness did not change the strength or direction of our estimates. Unlike other surgical trials, we did not undertake a modified ITT 142 (excluding the 10 randomisations in error and those withdrawn at point of randomisation) or a per-protocol analysis, although the compliance-based approach does provide a realistic estimate of those who complied with treatment.…”
Section: Participant Retentionmentioning
confidence: 99%
“…Costa et al (Costa et al, 2020) measured the Achilles Tendon Rupture Score, quality of life, complications and resource use of patients receiving non-operative treatment for an Achilles tendon rupture treated with plaster cast compared with those treated with functional bracing. They found that early weightbearing in a functional brace provides similar outcomes to traditional plaster casting and is safe for patients receiving nonoperative treatment of Achilles tendon rupture.…”
Section: Conservative Management Of Achilles Tendon Rupturementioning
confidence: 99%